2014
DOI: 10.1186/1752-0509-8-47
|View full text |Cite
|
Sign up to set email alerts
|

Fast Bayesian inference for gene regulatory networks using ScanBMA

Abstract: BackgroundGenome-wide time-series data provide a rich set of information for discovering gene regulatory relationships. As genome-wide data for mammalian systems are being generated, it is critical to develop network inference methods that can handle tens of thousands of genes efficiently, provide a systematic framework for the integration of multiple data sources, and yield robust, accurate and compact gene-to-gene relationships.ResultsWe developed and applied ScanBMA, a Bayesian inference method that incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 47 publications
(67 reference statements)
2
92
0
Order By: Relevance
“…We performed a multistep validation of our pipeline by testing first, GENIST's DBN inference step, and next, the incorporation of clustering into the algorithm, as the inference step and its integration with clustering had never been tested. Accordingly, we tested GENIST's inference step with in silico time-series datasets (DREAM 4 challenge 2) (22-24) and found that, in terms of precision and area under the precision recall curve (AUPRC), our algorithm outperformed previously published methods [ebdbnet (25), ScanBMA (26), ARACNE (27), CLR (28) . Furthermore, we validated the integration of the clustering and inference steps by testing the performance of both GENIST's inference step alone, as well as together with clustering of coexpressed genes across distinct cell types.…”
Section: Resultsmentioning
confidence: 99%
“…We performed a multistep validation of our pipeline by testing first, GENIST's DBN inference step, and next, the incorporation of clustering into the algorithm, as the inference step and its integration with clustering had never been tested. Accordingly, we tested GENIST's inference step with in silico time-series datasets (DREAM 4 challenge 2) (22-24) and found that, in terms of precision and area under the precision recall curve (AUPRC), our algorithm outperformed previously published methods [ebdbnet (25), ScanBMA (26), ARACNE (27), CLR (28) . Furthermore, we validated the integration of the clustering and inference steps by testing the performance of both GENIST's inference step alone, as well as together with clustering of coexpressed genes across distinct cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Then, model-based methods use the learned parameters (coefficients) of regulators as regulatory interaction scores. Ridge regression, LASSO and Bayesian Model Averaging (BMA) are some of the representative methods of model-based methods [14, 15, 18, 19]. BGRMI, a recently developed GRN inference method, computes regulatory interaction scores using posterior probabilities obtained by BMA [18].…”
Section: Introductionmentioning
confidence: 99%
“…Various frameworks have been proposed for identifying gene regulatory networks including Boolean networks [1,2], neural networks [3], differential equations [4], factor graphs [5] and Bayesian networks [6,7,8]. Among these approaches, Bayesian dynamical networks have been particularly popular [9,10,11].…”
Section: Introductionmentioning
confidence: 99%